Genealogy of Umayyad domination over Iranian identity: Analysis of the Arab-Islamic dispositif - Afshin Eshkevar Kiaei (رهیافتهای سیاسی و بین المللی)
The Arabs with the new spiritual force of Islam, despite claiming to be a world religion and independent of ethnicity, tribe, nation and race, after many conquests claimed special ethnic groups and tribes. Boasting about this, they claimed that they had a divine mission. According to this claim, they said that they should spread this identity in other lands as well, including the territory of Iran. After the conquest of Iran and the consolidation of their power, the Arabs (especially the Umayyads) used various strategies to dominate and exercise power over the Iranians; Such as the threat of the use of coercive means, the persuasive effects of speech, economic inequalities, the use of more or less complex means of control. Based on this, the question that this research wants to answer is what was the type and manner of Umayyad domination over the Iranians and what tools did they use for this domination? To answer this question, we have used the method of Michel Foucault's historical genealogy. While explaining the different strategies of the Umayyads for domination and exercising power over the identity of Iranians, we have tried to refer to both the events of discourse and non-discourse actions for this domination and exercise of power.